Public health monitoring and research: experience with electronic health record data - Zucker, Rachel, author; Society of Quality Assurance, publisher (Colorado State University. Libraries, 2016)
This talk will describe the software underlying CHORDS, the concept of a federated query, the methods CHORDS uses to enable site participation, and the formal agreements required to contribute to the network or query distributed data. Finally, we will discuss growth of this technology platform and anticipated needs and challenges as CHORDS serves new use cases to enable clinical health research studies and other research activities. A key challenge is the need for patient record linkage to unduplicate an individual's medical records across systems. A solution underway seeks to transfer data to an external partner to leverage an existing master patient index tool used for clinical care.
Presented at the National data integrity conference: data sharing: the how, why, when and when not to share held on June 2-3, 2016 at University of Colorado, Denver, Colorado. The National Data Integrity Conference is a gathering of people sharing new challenges and solutions regarding research data and integrity. This conference aims to provide attendees with both an understanding of data integrity issues and impart practical tools and skills to deal with them. Topics addressed will include data privacy, openness, policy, education and the impacts of sharing data, how to do it, when to do it, and when not to. Speakers and audience members come from diverse fields such as: Academic Research; Information Technology; Quality Assurance; Regulatory Compliance; Private Industry; Grant Funding; Government.
PowerPoint presentation during Lightning Talks given on June 3, 2016.
Rachel is affiliated with the University of Colorado - Anschutz Medical Campus.
Keywords: CHORDS; Colorado health observation regional data service; data sharing and aggregation; PopMedNet; data sharing governance